First Study of the Prevalence and Characterization of Brachial Plexus Injuries in Guatemala - González Lemus, Carmen Joanna; Romero Prieto, Fernando Xavier (Journal of Brachial Plexus and Peripheral Nerve Injury, 2021)
Objective This study aimed to estimate the prevalence of brachial plexus injuries and to characterize clinically and epidemiologically patients with brachial plexus injury.Materials and Methods In this cross-sectional descriptive study, 2,923 medical records of patients aged 1 to 64 years who presented at outpatient peripheral nerve unit of the Orthopedic Surgery Department of Hospital Roosevelt, Guatemala, from January 2017 to December 2017, were prospectively analyzed to identify the prevalence and factors associated with brachial plexus injuries.Results The prevalence rate of brachial plexus injuries in patients was 5.74%. This injury is more common in men (90.5%) aged 24 to 64 years. Brachial plexus injuries occurred secondary to motorcycle accident in 72% of the cases, with the majority affecting the dominant upper extremity. In addition, 64.28% of the patients took 1 to 6 months to seek consultation, whereas only 16.07% requested medical assistance <1 month from the onset of symptoms, and this result was associated with early diagnosis and adequate recovery during follow-up. Furthermore, 66.67% presented upper brachial plexus injury with no associated fractures or vascular injury, manifesting distress while performing daily activities that required hand, arm, and elbow movements.Conclusion The risk of suffering BPIs in Guatemala increases in economically active male patients that use motorcycles as main mode of transportation. Patients should consult immediately after injury onset to optimize management results. For this reason, hospitals must develop specialized clinical guidelines to speed up the identification and treatment of BPI injuries.
Keywords: brachial plexus; injury; prevalence; characterization; upper extremity